2023
DOI: 10.31083/j.fbl2803061
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Coenzyme Q Redox Homeostasis and Reactive Oxygen Species Production

Abstract: Mitochondrial coenzyme Q (mtQ) of the inner mitochondrial membrane is a redox active mobile carrier in the respiratory chain that transfers electrons between reducing dehydrogenases and oxidizing pathway(s). mtQ is also involved in mitochondrial reactive oxygen species (mtROS) formation through the mitochondrial respiratory chain. Some mtQ-binding sites related to the respiratory chain can directly form the superoxide anion from semiubiquinone radicals. On the other hand, reduced mtQ (ubiquinol, mtQH2) recycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 125 publications
0
4
0
1
Order By: Relevance
“…Along with activities such as those of cytochome c peroxidase that remove hydrogen peroxide, electron transport itself is a major source of ROS [46]. At a higher degree of reduction of its electron carriers, ROS production in the respiratory chain tends to increase [47]. We hypothesize that the downregulation of the respiratory promoters and the decrease in NADH oxidase activity that we see under ethanol stress are aimed primarily at minimizing respiratory ROS production.…”
Section: Discussionmentioning
confidence: 86%
“…Along with activities such as those of cytochome c peroxidase that remove hydrogen peroxide, electron transport itself is a major source of ROS [46]. At a higher degree of reduction of its electron carriers, ROS production in the respiratory chain tends to increase [47]. We hypothesize that the downregulation of the respiratory promoters and the decrease in NADH oxidase activity that we see under ethanol stress are aimed primarily at minimizing respiratory ROS production.…”
Section: Discussionmentioning
confidence: 86%
“…Mitochondria are the main sites of ROS production, and structural damage or dysfunction of these organelles can easily disrupt the in vivo balance and induce oxidative damage [ 35 ]. Harmful stimuli alter the permeability of the mitochondrial membrane, reduce membrane potential, block the transmission of the mitochondrial electron transport chain, inhibit the production of cytochrome c, inhibit the levels of adenosine triphosphate and accelerate the accumulation of total ROS in cells [ 36 ]. Based on the finding that aFGF could ameliorate oxidative stress in the wounds of animal models, this study confirmed that high glucose could induce abnormal changes in the MMP and the accumulation of mtROS and ROS in an in vitro high-glucose-induced VE cell model.…”
Section: Discussionmentioning
confidence: 99%
“…C , from ambiguous NADH-FADH 2 analogy ( 73 ) to ( D ) graphical misconception ( 58 ), as in ref. ( 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ...…”
Section: The Fadh 2 - Fad Confusion In the Succina...unclassified